0654 PSG AND MSLT CHARACTERIZATION OF REM SLEEP WITHOUT ATONIA AND REM BEHAVIOR DISORDER AMONG PEDIATRIC PATIENTS WITH NARCOLEPSY - Bin-Hasan, S; Maski, K (Sleep (New York, N.Y.), 2017)
Abstract Introduction: In this study, we aim to determine the prevalence of nocturnal RWA and RBD in a drug-naïve pediatric narcolepsy population and compare findings to pediatric patients with other central nervous system hypersomnias and controls. We additionally aim to determine the prevalence of RWA and RBD during daytime REM bouts captured during MSLT testing. Given that RSWA, RBD and cataplexy are thought to underlie dysfunction within REM on/off neurons, we hypothesize that RSWA and RBD will be found only during the daytime and nighttime REM periods among patients with narcolepsy type 1. Methods: Based on sleep study results and clinical history, we grouped subjects as narcolepsy type 1 (N1, n=11), narcolepsy type 2 (N2, n=4), idiopathic hypersomnia (IH, n=5) and controls (C, n=11). Mean age of patients was 13 years and 49% were female. RSWA and RBD were scored based on American Academy of Sleep Medicine specifications. We calculated a RSWA index for each subject (number of REM epochs with RSWA/total REM epochs). Results: On the PSG, we only detected RBD among N1 patients (2/11, 18%) but found no difference in the frequency of RSWA among groups (P=0.18). Notably, all N1 patients had RSWA and the RSWA index was 5.5x higher on their nocturnal PSGs compared to all other groups (P=0.002). On MSLT, 82% of N1 patients had RSWA and RSWA was not detected in any other groups. The two N1 patients with RBD during the PSG also had RBD on the MSLT. Conclusion: RSWA is uniquely detected among N1 patients on the MSLT but not the PSG. However, the frequency of nocturnal RSWA is markedly higher in N1 pediatric patients compared to other groups, findings consistent with adult narcolepsy data. Our findings have practical implications about scoring pediatric MSLTs as epochs of REM may lack the classic atonia in N1. Furthermore, the frequent presence of RSWA across day and night REM periods and higher mean RSWA index in the N1 group suggest that greater hypocretin loss results in phenotypic changes in REM sleep in addition to dysregulated REM sleep bouts. Support (If Any): None.